Institutional hybridity and cultural isomorphism in contemporary policing. (December 2019) - Cockcroft, Tom
Recent work on policing has increasingly acknowledged the influence of a broad array of changes upon both the structure and culture of police organizations. Generally, however, literature and research have tended to focus attention onto those elements of the broader police environment that effect such developments, whereas little commentary, to date, has been directed towards those features which impact across the broader public sector. Through drawing on the concepts of 'hybrid professionalism' [Noordegraaf M (2015) Hybrid professionalism and beyond: (new) forms of public professionalism in changing organizational and societal contexts. Journal of Professions and Organization 2: 187–206] and 'institutional isomorphism' [DiMaggio PJ and Powell WW (1983) The iron cage revisited: Institutional isomorphism and collective rationality in organizational fields. American Sociological Review 48: 147–160], this conceptual paper will argue that the impact of neoliberal ideology on the contemporary public sector has created a police organization for which professionalism increasingly denotes generic management skills that are common across different occupations and different police roles. In particular, it will be suggested that such institutional isomorphism may drive ideational responses commensurate with cultural change within police organizations. In short, therefore, the paper will make the case that, in parallel with changes already identified by other academics, broader structural changes may lead to a narrower and more generic set of cultural responses within contemporary police organizations.